PENINGKATAN KEWIRAUSAHAAN MELALUI PENGLOLAAN SAMPAH DI PADUKUHAN SEGOROYOSO 1 PLERET BANTUL YOGYAKARTA - Hidayatullah Hidayatullah; Ary Subiyantoro; Purwanta Purwanta; Suliantoro Suliantoro (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
Garbage, which has always been a crucial problem in society, still has economic value when managed properly. The limited infrastructure owned by the government requires the community to independently play an active role in managing waste. Through a community service program entitled increasing entrepreneurship through waste management in Segoroyoso 1 Pleret Bantul Yogyakarta. This program is carried out on the grounds that there are still many people who know how to manage it properly. In addition, this program also fosters an entrepreneurial spirit in the community by utilizing waste as the main capital. From the reasons the authors formulate several issues: 1. How to properly manage waste in accordance with government recommendations?.2. How to make waste as a field of entrepreneurship that has a sale value? The methods used in community service are observation, interviews, lectures, practice and documentation. From the results of this service it was found that waste management in the Segoroyoso1 Pleret Bantul Yogyakarta community is good, but it still requires special handling, especially for home-based businesses or MSMEs that are medium to upper scale, because they have to be supported by waste management tools that are expensive. For waste management to become a business area, progress has been made even though it needs to be improved again